Improvement of coordination abilities of qualified athletes specializing in fencing - Lopatenko, G.; Vynogradov, V.; Yasko, L.; Cherhenko, G. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. The aim of the research is to investigate the efficiency of designed complexes of training exercises aimed to improve the coordination abilities of qualified athletes in fencing. Material and Methods. 22 qualified athletes specializing in fencing aged from 15 to 18 took part in the research. The study design included the sequential pedagogical experiment that was realized through the several stages. At the first stage, the preliminary testing of the athletes` coordination abilities (n=22) was conducted. During the preliminary testing the following tests were applied: jumps to the line; shuttle run (4x9 m.); T-test, straight touch from en-garde position to the target of 10 cm in diameter from close range (10 attempts); straight lunge attack from en-garde position to the target of 10 cm (10 attempts). At the second stage of the pedagogical experiment two complexes of exercises aimed at developing the coordination abilities of the athletes were applied for 3 months. The experimental complexes of exercises were used twice a week. At the third stage, the efficiency of experimental complexes aimed at the developing of coordination abilities of qualified athletes in fencing was checked through a control testing. The Statistica 10 software created by the StatSoft Company was used for statistical processing of data. Results. It was established that during the process of coordination abilities development, the greatest attention should be given to the athletes` ability to control timing, spatial and physical parameters of moves and moves consistency. To improve the process of developing the coordination abilities of the qualified athletes in fencing two complexes of training exercises were developed. The results of the pedagogical experiment confirmed the statistical differences in the levels of the athletes` coordination abilities manifestation before and after using experimental training complexes (p<0.05). Conclusions. It has been shown that specially developed training complexes could be used during the training process in order to develop and increase the level of coordination abilities of qualified athletes in fencing. The analysis of experts` opinion showed that the development of coordination abilities in fencing should be oriented towards the development of athletes` ability to control timing, spatial and physical parameters of movements.